Effectiveness of cognitive rehabilitation for people with multiple sclerosis: a meta-synthesis of patient perspectives - Klein, Olga A.; Drummond, Avril E.R.; Mhizha-Murira, Jacqueline R.; Mansford, Laura; das Nair, Roshan (Routledge Open Select, 2017)
While previous randomised controlled trials and meta-analyses offer only limited evidence for the effectiveness of cognitive rehabilitation, qualitative studies examining patient perspectives report more positive outcomes. This meta-synthesis of qualitative studies examined patient perspectives of cognitive rehabilitation for memory, attention, and executive function problems in people with multiple sclerosis. Using set eligibility criteria, we screened electronic databases, reference lists, and academic networks for relevant papers. Seven papers (195 participants) were selected. Two independent researchers conducted quality appraisals of papers. Data analysis, guided by the thematic synthesis approach, yielded six main themes. These suggested that patients benefitted from the group environment in rehabilitation. Cognitive rehabilitation facilitated the participants’ reflection and awareness of their cognitive deficits, and was associated with increased knowledge and understanding of their illness. Increased strategy use was reported and associated with improvements in cognitive functioning and greater confidence and perseverance. Participants reported emotional and social improvements, and felt more optimistic. Overall, these changes had a positive impact on participants’ quality of life. This synthesis of qualitative studies indicates that people with multiple sclerosis who experience cognitive deficits benefit from cognitive rehabilitation programmes. This finding must, however, be viewed in light of the limitations of this meta-synthesis. The meta-synthesis was registered in the PROSPERO database under CRD42017040148.